Drug interactions of oral anticoagulants - Anil, Gayathri; Muraleedharan, Pradhyumna; Faruqui, Atiya Rehman (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Oral anticoagulants (OACs) are the drugs of choice where long-term anticoagulation is needed due to convenience of dosing. But their use has potential for several drug interactions. Monitoring for potential interactions with timely management will decrease the risk of complications of anticoagulation. Methods: We aimed to assess the presence of potential drug-drug interactions in patients on oral anticoagulants for various indications. Prescriptions of a cohort of patients on oral anticoagulants were analyzed. Potential drug interactions were identified using free software available at www.drugs.com and classified into major, moderate and minor types. Results: Of the 135 patients in the study, 83 were males and mean age was 52.9±17.3 years. Most commonly used OACs were vitamin K antagonists (VKAs) (80.0%) followed by direct oral anticoagulants (DOACs) (20.0%). Median number of concomitant medications per patient was 4 (IQR 3-6). A total of 307 potential interactions were identified in 121 patients with a median of 2 interactions per patient. Of the 56 patients who had potential for major drug interactions, 45 (41.6%) were on VKAs and 11 (40.7%) on DOACs had potential to develop major interactions. Using logistic regression model, significant predictors of major drug interactions were age>60 years (OR 2.50; 95% CI 1.05-5.95; p=0.04) and presence of venous thromboembolism VTE (OR 0.09; 95% CI 0.02-0.55; p=0.01). Conclusions: This hospital-based study showed potential drug interactions with OACs. Age more than 60 years and presence of VTE were significant predictors of major interactions. Awareness of potential interactions and monitoring doses of OACs help to prevent complications of therapy.